A new species of burrowing wolf spiders (Araneae: Lycosidae: Lycosa) from Iran - Nadolny, Anton A.; Zamani, Alireza (Zootaxa, 2017)
With over 2400 species in 123 genera, Lycosidae is one of the largest spider families (WSC 2017). For over two hundred years, the type genus Lycosa Latreille, 1804 have accumulated large-sized wolf spiders from all over the world. Thus, with 218 nominal species, this genus is distributed in all zoogeographical regions (WSC 2017). Almost none of the species currently classified in Lycosa appear to be related to the type species—L. tarantula (Linnaeus, 1758); hence, the genus is polyphyletic and should be divided into several genera. This process has been already started; for example, in Australia and New Zealand where many of large wolf spiders have been removed from Lycosa (Roewer 1955, 1959, 1960; Vink 2002; Framenau & Baehr 2016). Also, some Holarctic, Neotropic and Afrotropic species were transferred from Lycosa to other genera (for a complete list of references see WSC 2017). In the Palaearctic, Lycosa is represented by 60 species (WSC 2017) and remains almost unrevised. From the southern Palaearctic, Saharo-Gobian desert region (Yemel’yanov 1974), 36 species of Lycosa have been recorded to date, 6 of which are poorly described (WSC 2017).